Network structure and properties of crosslinked bio-based epoxy resin composite: An in-silico multiscale strategy with dynamic curing reaction process. (August 2021) - Wang, Yan; Gan, Han-Lin; Liang, Chi-Xin; Zhang, Zhong-Yan; Xie, Mo; Xing, Ji-Yuan; Xue, Yao-Hong; Liu, Hong
Abstract: A multiscale simulation strategy was proposed to study the curing reaction on the network formation and corresponding mechanical properties of a bio-based epoxy resin composite. The crosslinking process of the system to form an epoxy network structure was reproduced on the mesoscopic scale by the dissipative particle dynamics simulation coupled with a curing reaction model. The density functional theory (DFT)-based method, IRC and relaxed potential energy surface scanning calculations were combined with the reverse mapping operations in order to improve the overall quality the reverse mapped structures. Finally, molecular dynamics simulations were performed on the atomistic level to analyze the mechanical properties, the volume shrinkage and the glass transition of the bio-based epoxy resin system, etc. This multiscale simulation strategy can provide as a possible investigation scheme for the subsequent improvement and design of bio-based epoxy resin composite materials. Graphical abstract: Image, graphical abstract